2006
DOI: 10.1021/ol062244f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Racemic Secondary Alcohols Catalyzed by Chiral Diaminodiphosphine−Ir(I) Complexes

Abstract: Chiral diaminodiphosphine-Ir(I) complexes were found to efficiently catalyze enantioselective oxidation of racemic secondary alcohols in acetone. In the presence of base, oxidative kinetic resolution of the alcohols proceeded smoothly with excellent enantioselectivity (up to 98% ee) under mild conditions. [reaction: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…In 2006, Gao et al. reported that chiral diaminodiphosphine‐Ir(I) complexes of 36 efficiently catalyzed the KR of secondary arylalkanols with excellent enantioselectivities of up to 98% ee under mild conditions 83. In the presence of a base such as KOH in acetone, the process allowed selectivity factors of up to 34 to be reached (Scheme ).…”
Section: Kinetic Resolution Of Alcoholsmentioning
confidence: 99%
“…In 2006, Gao et al. reported that chiral diaminodiphosphine‐Ir(I) complexes of 36 efficiently catalyzed the KR of secondary arylalkanols with excellent enantioselectivities of up to 98% ee under mild conditions 83. In the presence of a base such as KOH in acetone, the process allowed selectivity factors of up to 34 to be reached (Scheme ).…”
Section: Kinetic Resolution Of Alcoholsmentioning
confidence: 99%
“…[17][18][19][20][21] Recently, researchers have developed several effective non-enzymatic catalysts for the oxidative kinetic resolution (OKR) of racemic alcohols. [22][23][24][25] In the last two decades, different chiral ligands with palladium, [26][27][28][29][30][31][32] ruthenium, [33][34][35] iridium, 36,37 cobalt, 38 iron, 39 and manganese (Mn) metal ions have been used as catalysts for OKR of racemic secondary alcohols. In particular, chiral Mn(III) salen complexes are considered to be the most effective catalyst for the OKR of racemic secondary alcohols ( Figure 1) because of their facile synthesis and catalytic reaction condition with high turnover frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many processes known, the oxidative kinetic resolution (OKR) of racemic secondary alcohols is a particularly attractive and efficient method [12][13][14][15]. Several chiral complexes pre-prepared or generated in situ from the corresponding chiral ligands with Pd [16][17][18][19][20][21][22], Ru [23][24][25], Ir [26][27][28], Co [29], Fe [30], and Mn [31][32][33][34][35][36][37][38][39] ions have been used as catalysts for the OKR of racemic secondary alcohols. Among these metal complexes, chiral Mn(III)-salen complexes [31][32][33][34][35][36][37] are of special interest due to their easy synthesis, mild reaction conditions and very short reaction time.…”
Section: Introductionmentioning
confidence: 99%